Phosphite uptake and distribution in potato tubers following foliar and postharvest applications of phosphite‐based fungicides for late blight control. (16th November 2016) - Borza, T.; Peters, R.D.; Wu, Y.; Schofield, A.; Rand, J.; Ganga, Z.; Al‐Mughrabi, K.I.; Coffin, R.H.; Wang‐Pruski, G.
Abstract: Foliar and postharvest applications of phosphite (Phi)‐based fungicides are used to control the oomycete Phytophthora infestans which is responsible for the occurrence of late blight in potatoes. Optimisation of the usage of Phi‐based fungicides for disease control during the growing season and in subsequent storage can lead to improved potato production and processing quality. In order to assess the efficiency of Phi translocation to tubers, following foliar and postharvest treatments of potato crops with the Phi‐based fungicides, the amount of Phi in tubers was determined by a high‐performance ion chromatography method. The quantity of Phi found in tubers increased with the total amount of Phi‐based fungicides applied during the growing season. Foliar applications of Phi resulted in an uneven distribution of Phi in the three tuber regions analysed, with high concentrations being identified in the tuber cortex (32.5–166.4 µg g −1 fresh tissue) and medulla regions followed by the skin area. Postharvest treatment of tubers led to a different distribution of Phi, with the highest concentrations of Phi found in the skin (411.0–876.6 µg g −1 fresh tissue) followed by the cortex and medulla regions. As foliar treatments are essential to protect the aerial parts of the plants during the growth season, the best disease management practices of tubers should include the postharvest treatment in addition to foliar applications. The use of both types of treatments ensures that concentrations of Phi in excess of 100 µg g −1 fresh tissue are present in tuber skin and cortex areas; such concentrations are needed to suppress the growth of P. infestans on tubers during storage.